Analysis Of the Level Of Community Compliance With Implementation Of The Covid-19 Health Protocol (Literature Review) - St. Hateriah; Esti Yuandari (Jurnal EduHealth, 2022)
Corona virus disease 2019 (Covid-19) is a new type of disease that has never been previously identified in humans. The virus that causes Covid-19 is called Sars-CoV-2. Health protocil as an effort to prevent covid-19. Compliance with health protocols is the main thing in preventing Covid-19. The importance of compliance in impementing the Covid-19 preventive health protocol. This research used a descriptive research type with a literature review design. The studies carried out in the preparation of the research referred to the 10 latest articles in 2020 and 2021 which discuss issues of compliance with the implementation of Covid-19 health protocol. This study aims to determine the level of public compliance with health protocols during the Covid-19 pandemic in order to prevent the spread of Covid-19. The 10 articles show that the research has the same goals and the same results, so it can be concluded that the community has not fully complied with health protocols in a effort to suppress the spread of Covid-19